Optimal dimensions of steel welded beams with hinged support units - G. M. Bazhin (Vestnik MGSU)
Introduction. At the present time, the requirements to reliability and durability of steel structures, as well as their economic feasibility, are increasing. Considering the complexity of analyzing multiple factors influencing the strength, stability and durability of steel welded beams, a new approach to the determination of optimal dimensions based on maximum-strain-energy theory is proposed, with the derivation of new coefficients to simplify the selection of beam cross-sections.Materials and methods. The research involved an analysis using maximum-strain-energy theory, with the application of which the potential energy of elastic deformation of steel welded beams was calculated. To determine the optimal dimensions of beams, the first derivative of the potential energy of elastic deformation over the height of the beam was calculated to establish the optimal dimensions of the beams, and the obtained result made it possible to compute the ratio of the height and thickness of the beam web to the width and thickness of the beam girdle. This ratio is denoted by the coefficient kopt, by means of which a methodology for selecting the optimal beam cross-section is proposed.Results. Formulas were derived which allow to select the optimal beam section quickly and with the least weight using the coefficient kopt and web flexibility. Iterative calculations were used to determine the optimal values of the coefficient kopt and flexibility under different loads and beam spans. As a result of the research, formulas for determining kopt were derived, depending on the distributed load q, along with graphs and tables for determining the optimal web flexibility and the kopt coefficient for the given parameters.Conclusions. Based on the conducted analysis, a method of selecting the optimal dimensions of steel welded beams was formulated, based on maximum-strain-energy theory and the introduction of the kopt coefficient. The developed formulas and iterative calculations, the results of which are presented in tables, make it possible to provide a quick and metal-intensive selection of the optimal cross-section of welded beams under different loads and spans, significantly simplifying the design process and increases the efficiency of the use of materials and structures.